2019
DOI: 10.3233/kca-190068
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Survival Outcomes in Non-Metastatic Renal Cell Carcinoma in Latin America and Spain: A Multicentric Analysis

Abstract: Background: Renal cell carcinoma (RCC) is a lethal neoplasia. Data from Latin America are scarce, and the distinct ethnic origins of this population could affect predictive or prognostic factors. Objective: We aim to describe a large cohort of non-metastatic renal cell carcinoma, identifying the demographic, clinical, and pathological prognostic factors for survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
3
2
1
Order By: Relevance
“…A multi-institutional large retrospective study of 5670 patients over 36 years who underwent radical or partial nephrectomy from seven Latin American countries and Spain reported by Zequi et al found the 5-year survival for RCC to be 86.1%. 22 The five-year survival rate of our study was 62.8%, which is lower than the survival rate mentioned above. About 26.2% of the cases were diagnosed with metastatic disease, and a further 6% progressed to metastatic cancer despite surgical resection.…”
Section: Discussioncontrasting
confidence: 72%
“…A multi-institutional large retrospective study of 5670 patients over 36 years who underwent radical or partial nephrectomy from seven Latin American countries and Spain reported by Zequi et al found the 5-year survival for RCC to be 86.1%. 22 The five-year survival rate of our study was 62.8%, which is lower than the survival rate mentioned above. About 26.2% of the cases were diagnosed with metastatic disease, and a further 6% progressed to metastatic cancer despite surgical resection.…”
Section: Discussioncontrasting
confidence: 72%
“…CCRCC is the most common subtype and PRCC is the second most common subtype in RCC. ChRCC accounts for 4-6% of all RCC 4 . Diagnosis of cases were 78,8% CCRCC, 15,1% PRCC and 6,1% ChRCC in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sağkalım ile yaş ve tümör çapı arasında ters ilişki bulunmaktadır 3 . Metastatik lenf nodu, tümör nekrozu ve çevre yağ doku invazyonu kötü prognoz ile ilişkilidir 4 . Bu çalışmaya 179 renal hücreli karsinom vakası dahil edildi.…”
Section: öZunclassified
See 1 more Smart Citation
“…While small and localized tumors have a high 5-year relative survival rate at 93%, it drops down significantly when metastases develop to only 12% [6]. Due to the fact that about a third of RCCs are diagnosed at IV (metastatic) stage and 20-50% of pre-metastatic cases will progress to stage IV regardless of surgical excision, the RCC is considered the deadliest urological cancer [7]. The most common type of RCC at 75% occurrence rate is clear cell RCC (ccRCC), followed by papillary RCC (16%) and chromophobe RCC (7%).…”
Section: Rcc -A Brief Overviewmentioning
confidence: 99%